2008
DOI: 10.3233/jad-2008-14304
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Placebo Group Decline in the Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog) in 24 Week Clinical Trials of Alzheimer's Disease

Abstract: One limitation of several recent 24 week Alzheimer's disease (AD) clinical trials was the lack of cognitive decline detected by the AD Assessment Scale-cognitive subscale (ADAS-cog) in the placebo groups, possibly obscuring true medication effects. Data from 733 individuals in the placebo arms of six AD clinical trials performed 1996-1997 were pooled to examine the relationship of clinical, demographic, and genetic characteristics with the 24 week change in ADAS-cog. Baseline cognitive and functional status an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…Although mean ADAS-Cog values in the placebo groups in the current studies declined over time, the magnitude of the decline was less than reported in historical studies in this population [42][43][44]. The challenges and potential limitations of current assays for measuring cognitive changes have been explored as significant limitations in several clinical investigations in mild-to-moderate disease [45,46]. Furthermore, the ADAS-Cog was developed to test efficacy of AChEIs in subjects with AD, and although widely used to assess the efficacy of therapies with other mechanisms of action, inherent limitations should be considered.…”
Section: Discussioncontrasting
confidence: 62%
“…Although mean ADAS-Cog values in the placebo groups in the current studies declined over time, the magnitude of the decline was less than reported in historical studies in this population [42][43][44]. The challenges and potential limitations of current assays for measuring cognitive changes have been explored as significant limitations in several clinical investigations in mild-to-moderate disease [45,46]. Furthermore, the ADAS-Cog was developed to test efficacy of AChEIs in subjects with AD, and although widely used to assess the efficacy of therapies with other mechanisms of action, inherent limitations should be considered.…”
Section: Discussioncontrasting
confidence: 62%
“…The limitations of this study include those inherent in investigations of AD: a limitation on treatment duration for a placebo-controlled study in a significantly ill population [36] ; variability in AD progression [56] , and the use of assessment tools that may be inadequate for detecting drugs with a modest treatment effect in a mildto-moderate AD population [46,57] . The ADAS-Cog was chosen as an assessment in this study, based on published outcomes for the active control donepezil, and on its widespread use in evaluating new therapies for AD.…”
Section: Discussionmentioning
confidence: 99%
“…The ADAS-Cog may be more sensitive to disease progression and treatment effects in moderate versus mild AD [46] , and a post hoc analysis was performed to analyze whether treatment effects in this study differed by baseline MMSE scores (i.e. in subjects with moderate versus mild AD).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Those with probable AD and mild to moderate dementia were diagnosed by Dubois criteria 11 Mini-Mental State Examination (MMSE) and the Alzheimer's Disease Assessment Scale-cognitive subscale were conducted as described. 12,13 Twenty-four of the 26 cross-sectional patients with AD were taking an acetyl-cholinesterase inhibitor and/or memantine, and 5 were on antidepressant medications.…”
mentioning
confidence: 99%